Direct Photoinduced Electron Transfer from Excited State of Rhodamine B for Carbon-Radical Generation - Yoshioka, Eito; Kohtani, Shigeru; Jichu, Takahisa; Fukazawa, Takuya; Nagai, Toyokazu; Takemoto, Yoshiji; Miyabe, Hideto (Synlett, 2015)
The photoinduced electron transfer (PIET) from the excited singlet state (S1) of rhodamine B to i-C3F7I smoothly proceeded in the presence of water. This process was supported by the fluorescence quenching of rhodamine B with addition of i-C3F7I in ethanol. The present method was applied to the atom-transfer radical reaction involving the cyclization step.
Keywords: radical reaction; cyclization; photochemistry; alkyl halides; fluorine